PENGARUH GREEN FINANCING DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA - Muhammad Aziz Ramadhani (PT SOLUSI EDUKASI BERDIKARI, 2025)
This study aims to analyze the effect of green financing on profitability and firm value, as well as the role of profitability as a mediating variable in manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative approach using secondary data obtained from annual financial statements and sustainability reports during the 2021–2024 period. The samples were selected using the purposive sampling method and analyzed through multiple linear regression. The results indicate that green financing does not significantly affect profitability or firm value, and profitability does not mediate the relationship between green financing and firm value. These findings suggest that the economic benefits of green financing tend to be long-term and have not been fully reflected in companies’ financial performance or market valuation.